Risposta del cortisolo salivare all`esercizio concomitante di forza e aerobico ad alta intensità: uno studio pilota - Panissa, L. G.; Franchini, E.; Julio, U. F.; Neves, R. X.; Seelaender, M.; de Souza, C. T.; Rodrigues, B.; Lira, F. S. (Medicina dello Sport, 2014)
Aim: The aim of this pilot study was to compare strength performance and salivary cortisol levels response during a single strength session, and a strength session after 30 min of high-intensity aerobic exercise (concurrent condition). Methods: Saliva was collected from 7 male subjects, before and after all exercise bouts, and the maximum number of repetitions (MNR) and total volume (TV) in the different conditions assessed. Results: The MNR and TV were reduced in concurrent condition compared with control condition. Strength exercise in the concurrent condition induced higher salivary cortisol in relation to strength exercise or to and high-intensity aerobic exercise, separately. Conclusion: The different salivary cortisol profile in response to concurrent exercise reflects the faster reactivity of the hypothalamic-pituitary-adrenocortical system in this circumstance.